ENT 600 : NPD Smart Intelligence Backpack (SiB) / Mohammad Amirulhaikal Mohamed Razali ... [et al.] - Mohamed Razali, Mohammad Amirulhaikal; Sharifuddin, Muhammad Aliff; Hussin, Haziq; Habbibollah, Muhammad Haziq; Eliasa', Muhammad Syazwan (2019)
Smart Intelligence Backpack (SiB) is a innovation backpack that equipped with the technological parts. This idea started with one of our team members who is a student and hikers. The problem is he always run out of its cellular battery during camping. Besides that, he is also need some safety accessories that can be used immediately during dangerous situation. There are many existing products in the markets that similar to this project but the accessories are not enough to fulfil the needs of the users. So, the purpose of this innovation is to create a backpack that easy to use, convenient, on-the-go charging for people who are outside their homes and provide more safety system through this SiB.